The past, present and future of secondary metabolite research in the Dothideomycetes - Muria-González, Mariano Jordi; Chooi, Y.; Breen, S.; Solomon, P. (Wiley-Blackwell Publishing Ltd., 2015)
© 2015 BSPP and John Wiley & Sons Ltd.Summary: The Dothideomycetes represents a large and diverse array of fungi in which prominent plant pathogens are over-represented. Species within the Cochliobolus, Alternaria, Pyrenophora and Mycosphaerella (amongst others) all cause diseases that threaten food security in many parts of the world. Significant progress has been made over the past decade in understanding how some of these pathogens cause disease at a molecular level. It is reasonable to suggest that much of this progress can be attributed to the increased availability of genome sequences. However, together with revealing mechanisms of pathogenicity, these genome sequences have also highlighted the capacity of the Dothideomycetes to produce an extensive array of secondary metabolites, far greater than originally thought. Indeed, it is now clear that we appear to have only scratched the surface to date in terms of the identification of secondary metabolites produced by these fungi. In the first half of this review, we examine the current status of secondary metabolite research in the Dothideomycetes and highlight the diversity of the molecules discovered thus far, in terms of both structure and biological activity. In the second part of this review, we survey the emerging techniques and technologies that will be required to shed light on the vast array of secondary metabolite potential that is encoded within these genomes. Experimental design, analytical chemistry and synthetic biology are all discussed in the context of how they will contribute to this field.